Research on PDC drilling parameter optimization based on dynamic drilling strategy - Zhou Dong; Li Jiyang; Xu Haitao (E3S Web of Conferences, 2023)
Drilling parameters optimization is very important for practical engineering drilling, and the rationality of the selected optimization mode directly affects the accuracy of the parameters obtained. The maximum bit performance curve which can reflect the relationship between the depth reached by a single bit and the maximum drilling speed is introduced, which provides a method basis for preparing multi-bit drilling program and dynamic drilling strategy. Through the dynamic drilling strategy, the optimal bit operation combination is provided, so as to achieve the minimum drilling cost in a long drilling interval. The study shows that dynamic drilling strategy as a new drilling optimization method has high cost-effectiveness. The calculation example shows that the design method saves 18% of the cost compared with the drilling optimization method, and 40% of the cost compared with the drilling process without optimization treatment.